Influence of Job Characteristics and Non-Physical Work Environment on Job Satisfaction at Biro Adm. Pemda Propinsi Jateng - Citra Lutfi Annajib; Rara Ririn Budi Utaminingtyas; Irawan - Malebra (Politeknik Negeri Semarang, 2022)
The purpose of this study was to determine the effect of job characteristics and non-physical work environment on job satisfaction of employees of the Biro Administrasi Pembangunan Daerah Sekretariat Daerah Provinsi Jawa Tengah. Collecting data by questionnaire, and observation. The scale used in this study is a Likert scale of 5. Using saturated sampling, the samples of this study were all employees of the Biro Administrasi Pembangunan Daerah, totaling 42 employees. The analytical method used in this study is multiple linear regression analysis, validity test, reliability test, classic assumption test, F test R square, and T-test. The results of this study indicated that job characteristics and non-physical work environment affect job satisfaction. Job Characteristics and Non-Physical Work Environment contributed 53.2%, while the remaining 46.8% was influenced by other variables not examined in this study. Because this study uses only two variables, this can be a weakness of the study. Therefore, it is recommended for further researchers to use other variables outside the study that affect job satisfaction by 46.8%